(untitled) (Povijesni prilozi (Historical Contributions), 2019)
Flags from Maria Theresa’s era had regulated guidelines that had to be obeyed in order to produce the most representative as well as the most typical baroque banners. The ongoing military reforms launched by Maria Theresa, in conjunction with state-governing reorganizations, are also mirrored in the Collection of Flags and Streamers at the Croatian History Museum. In particular, there are four main representative flags that, on the one hand, show the practice of exhibiting statehood statuses by means of dynastic symbols on battalion standards, and on the other indicate the iconographic significance of saints and beatified kings on ceremonial and commemorative banners. These instructions were all done under the impression of the baroque style, the Age of Enlightenment, and the turbulent time of confl ict in Maria Th eresa’s reign.